A tiny Drude scatterer can accurately model a coherent emitter in nanophotonics - Binkowski Felix; Burger Sven; Kewes Günter (Nanophotonics)
We add a missing element to the set of directly computable scenarios of light-matter-interaction within classical numerical Maxwell solvers, i.e., light scattering from hybrid systems of resonators and individual Fourier-limited emitters. In particular, individual emitters are incorporated as tiny polarizable and resonant spherical scatterers. This emitter model is based on well-known extremal properties of Mie modes. The spherical emitter is made from an artificial Drude metal with ϵ(ω)=ϵb−ωp2/(ω2+iΓω) ${ε}(ω )=ε_{b}-{ω }_{p}^{2}/({ω }^{2}+i{Γ }ω )$ . By tuning ϵ b and ω p we adjust the resonance frequency and the Fourier-limited linewidth and by adjusting Γ we may add non-radiative damping or dephasing. This approach automatically reproduces the ideal text book coherent scattering cross-section of Fourier-limited two level quantum systems of σ 0 = 3λ 2/(2πϵ out) which is not possible with typically used Lorentz permittivities which only mimic optical resonances. Further, the emitter’s linewidth adopts to the surrounding optical local density of states (LDOS). To demonstrate this we successfully benchmark our approach with prominent examples from the literature.